Sistem Pencarian dan Penyewaan Rumah Kost Berbasis Web dengan Pendekatan Agile - Sahambangun, Heny; Kembuan, Olivia; Krisnanda, Made (JOINTER : Journal of Informatics Engineering, 2025)
Information systems have a considerable impact on business development which is managed by each individual. As a means of information, the website has a very important role in marketing and business management In Tomohon City, especially Matani Satu Village, which is located in North Sulawesi Province, which is currently starting to develop. Boarding houses have a lot of potential as they increase the demand for temporary housing. The purpose of this research is to create an application that can help and make it easier for all people and boarding house owners to be able to connect with each other only through a website-based cellphone. The method used in this website is the Agile Development method which has six stages, namely, planning, implementation, software testing, documentation, implementation, maintenance using the programming languages PHP, xampp, javascript and visual studio. Testing this system using the Black box testing method to prove that the application is in accordance with the objectives of the researcher.